CAPITAL ASSET PRICING MODEL VERSUS ARBITRAGE PRICING THEORY MODEL: WHICH IS MORE ACCURATE FOR INVESTMENT? - Rosdiana Rosdiana; Muhammad Irfai Sohilauw (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
The food and beverage industry has become a focal point for investors, both domestically and internationally because it has the opportunity to provide greater returns. Mitigating investment risks with a thorough risk and return analysis is imperative, employing models like the Capital Asset Pricing Model (CAPM) and the Arbitrage Pricing Theory (APT). This study aims to assess the predictive accuracy of the CAPM and APT models concerning stock returns within the food and beverage sector. The research method utilizes quantitative data from secondary sources and a descriptive research approach; the study focused on 26 samples out of 89 food and beverage companies listed on the Indonesia Stock Exchange (IDX) from March 2020 to May 2023. The results indicate that the CAPM model outperforms the APT model, with market return variables emerging as the most reliable predictor for analyzing stock returns. Research discussion: 16 companies exhibited positive actual returns, while 11 experienced negative returns. This research is unique because it pioneered the assessment of accuracy between the CAPM and APT models, particularly within the context of food and beverage companies listed on the Indonesia Stock Exchange (IDX)